Bridging immunization gaps: lessons from Zambia’s 2024 measles–rubella supplementary immunisation activity - Mwale, Moses; Masumbu, Penelope; Chipimo, Peter Jay; Sakubita, Patrick; Phiri, Andrew; Matanda, Kennedy; Mwangilwa, Kelvin; Carcelen, Andrea; Mutembo, Simon; Masaninga, Freddie; Sakala, Jackob; Lugala, Peter Clement (Frontiers in Public Health, 2025)
Zambia’s 2024 Measles-Rubella Supplementary Immunization Activity (SIA), conducted from 23 to 28 September across all 116 districts, targeted children aged 9–59 months to address immunization gaps exacerbated by COVID-19 disruptions and responding to ongoing measles outbreaks. This community case study evaluates the effectiveness of microplanning, the feasibility of real-time digital monitoring, and the equity of reaching zero-dose children during Zambia’s 2024 Measles-Rubella SIA, using a mixed-method approach to inform scalable immunization strategies in resource-limited settings. Through comprehensive microplanning, strategic community engagement, and real-time digital monitoring, the campaign achieved 97% national coverage and reached 165,000 previously zero-dose children in underserved communities. Implementation utilized Google Sheets and Open Data Kit tools, with quality assurance through over 7,500 supervisory visits. Despite achieving high overall coverage, several challenges emerged: funding delays, logistical constraints in remote areas, and data quality issues. Key lessons include the necessity of timely funding disbursement, strengthened cold chain infrastructure, and rigorous data verification processes. Community involvement through local leadership engagement and radio campaigns proved essential to success, while digital monitoring enabled rapid adaptation to emerging challenges. This case study provides actionable insights for designing equitable immunization campaigns in resource-limited settings, supporting global measles and rubella elimination goals through evidence of effectively tailored, data-driven strategies.